Hubungan Personal Branding Musisi Nasional Mario G. Klau Sebagai Founder Terhadap Brand Image Production House Dari Rumah Tua Creative di Nusa Tenggara Timur - Putri Un Tanjung; Laura Lahindah (Publikasi Indonesia, 2025)
This study aims to analyze the relationship between the personal branding of national musician Mario G Klau as founder and the brand image of Production House Dari Rumah Tua Creative in East Nusa Tenggara. The research method uses a descriptive quantitative approach with survey techniques through questionnaires to 100 respondents domiciled in East Nusa Tenggara and knowledgeable about Mario G Klau. The independent variable is Mario G Klau’s personal branding which includes dimensions of popularity, credibility, attractiveness, and professionalism, while the dependent variable is Rumah Tua Creative’s brand image which includes dimensions of quality perception, value, reputation, and emotional image. Data analysis uses validity tests, reliability, classical assumptions, and multiple linear regression. The results show that there is a positive and significant relationship between Mario G Klau’s personal branding and Rumah Tua Creative’s brand image with a significance value of 0.00 (p<0.05) and a coefficient of determination (R²) of 0.676 or 67.6%. This indicates that the higher Mario G Klau’s personal branding, the higher Rumah Tua Creative’s brand image. Personal branding formed through reputation, musical expertise, and local cultural background has been proven to increase public trust in the Production House.